Analisis Perilaku Keuangan Mahasiswa di Kabupaten Jombang - Arini Diah Ayu Pristianti; Dhani Ichsanuddin Nur (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This study aims to determine the effect of financial knowledge, financial attitudes and hedonic lifestyle on the financial behavior of students in Jombang Regency. Sampling was used by purposive sampling technique in order to obtain 99 respondents. This study uses primary data obtained from respondents' answers to questionnaires (students in Jombang Regency). This research was tested with PLS (Partial Least Square) with SmartPLS software. The results showed that financial knowledge, financial attitudes and hedonic lifestyles can make a real contribution in improving the financial behavior of students in Jombang Regency.